Pengembangan Kurikulum PAI di RA Tunas Literasi Qur’ani Desa Tasik Malaya Kecamatan Curup Utara Untuk Membentuk Generasi Qurani - Hana Hhoiriah, Beta; Botifar, Maria; Deriwanto, Deriwanto (Yayasan Literasi Kita Indonesia, 2023)
Strategy is interpreted as a guideline for action in which it can be interpreted as a learning plan between teachers and students in realizing two-way communication in achieving predetermined goals. by enrolling their children in Islamic educational institutions such as RA Tunas Literasi Qur'ani. Raudhatul Athfal is a formal institution that carries out basic teaching of general knowledge and religion, especially the teaching of the main Qur'an and provides basic religious education to children of basic education age between 5-6 years old. The Qur'anic Generation is a generation that is always in touch with the Al-Qur'an and prioritizes it as a way of life every day. The Qur'anic Generation is the best Generation among the other Generations because it is always guided by the Al-Qur'an in thinking, speaking, behaving and acting